Liberating Learning: Insights into the Merdeka Curriculum Implementation - Nina Trisna; Yasir Arafat; Nuril Furkan (Jurnal Ilmiah Ilmu Administrasi Publik, 2024)
The Merdeka Curriculum is a key component of the Ministry of Education, Culture, Research, and Technology's Merdeka Belajar policy, aimed at enhancing the quality of education in Indonesia. This study investigates the implementation of the Merdeka Curriculum in educational institutions, specifically describing and analyzing its execution, impact on teacher performance, and the factors that either hinder or support its implementation. The research was conducted at SMA Negeri 3 Prabumulih, utilizing a qualitative research approach with data collected through interviews, observations, and document analysis. Data were analyzed using the interactive model analysis technique from Miles and Huberman. The findings revealed that: (1) The implementation of the Merdeka Curriculum has been effectively carried out, transitioning from an independent choice model to a shared independent implementation model; (2) The successful implementation is supported by the roles of the principal, teachers, educational staff, and other stakeholders; (3) The Merdeka Curriculum is applied in grades X and XI, while grade XII continues to follow the 2013 Curriculum due to the transitional period; (4) The implementation process involves the planning of operational curriculum documents, organizing resources, mobilizing learning activities, and monitoring through direction, guidance, and assistance.